A Cross Platform Mobile Application Development for Voice and Remote Control of Programmable Instruments [Programlanabilir Cihazlarin Sesli ve Uzaktan Kontrolü için Çapraz Platform Mobil Uygulama Geliştirme] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2020)
In engineering education, group experiments in which some students participate as an audience due to reasons such as high-cost laboratory equipment, increasing number of students and therefore insufficient number of devices affect students' learning negatively. On the other hand, the inability of disabled students who cannot use their hands effectively to participate in the experiments actively creates a different problem. In this paper, in order to eliminate these problems encountered in classical laboratory environments and to enable students with disabilities to do experiments independently, the developing an independent mobile application with increased accessibility in order to control the devices in real or remote laboratories and to observe the results via a mobile device with voiced commands are presented. The Apache Cordova Library was used to enable the mobile application can work platform independently. While developing this application, open source softwares are preferred to keep the cost at minimum. Controlling setups with voice commands without touching hands can bring an important advantage in slowing the spread of the coronavirus (COVID-19), which has spread rapidly among people as of June 2020 and negatively affects lifes all over the world. © 2020 IEEE.
Keywords: Apache Cordova Framework; Google Voice Recognition; Internet of Things; Remote Laboratory